A Study of Satisfaction and Commitment of Prea Wa Silk Buyers in Kalasin Province. - แสงภักดี, วรรณภา; ใจเมตตา, สุพัตรา; บรรจง, วิยะดา; ดีบุญมี, สุพจน์; จำปาแพง, มัลลิกา (KKBS Journal of Business Administration and Accountancy, 2019)
This study aimed to investigate the loyalty of consumers to online Purchase Prae Wa silk in Kalasin province. The data collection was online questionnaires. Which the sample size was 100. Found that: Most respondents were female between 20-30 years old, bachelor's degree, government officer/ state enterprise employee. Most state enterprises earn 10,001 - 20,000 baht per month. Who influences the purchase decisions of their own. In one year ago, has been bought by 1-2 times for their own use and buy it from the manufacturer, pay per below 10,000 baht. And known Prae Wa Silk Kalasin Province Over 2 years. The main factor is the pattern and buy to at Ban Phon. The perception of the products advertised Prea Wa Silk. Average score was 3.89. The distribution channels that affect the decision to buy silk products are classified in clear categories. With an average of 4.35. Marketing promotion and convenient payments are an average of 3.92. Satisfaction with Prae wa silk Satisfaction with the current silk yarn used in present day was 4.23. Brand commitment The promotion of other Prae wa silk yarns can not make up for the Prae wa silk new fabric. With an average of 3.92.